Evolution of the psychology of work and of accumulation - GINI, C. (PSL Quarterly Review, 2014)
The article deals with the sociology of labour. The author accepts the psychological criteria of differentiation of social groups and depicts the evolution of society and of the spirit of accumulation in relation to the changes that have occurred in the psychology of man the worker, throwing into relief the main stages of this development. The importance of this last stage - that of spontaneous and pleasurable work, of which the United States represents the most advanced type among the Caucasian peoples - is such as to induce the author to suggest once again the need for an economic science wider and more comprehensive than “bourgeois” economics, which he calls Integral Economics: this should be based on a more general theoretical outline covering the whole of the historical development of human psychology and institutions. JEL: J01, J20, Z13